KETEPATAN RAMALAN LABA PADA PROSPEKTUS PENAWARAN UMUM PERDANA - MEILY SURIANTI; NUR INDRIANTORO (Jurnal Bisnis dan Akuntansi, 1999)
This research examined the accuracy of profits forecasts in prospectuses of companies newly listing on the Jakarta Stock Exchnage. This research used 51 companies covered a wide range of industrial sectors except financial sector that listed in period 1994-1996 as samples. Accuracy is measured by forecast error, absolute forecast error and squared forecast error. The results showed that the level of forecast accuracy tend much better in comparison to other studies before. This research also tested six hypotheses cast accuracy and one hypothesis that expected squared forecast error as determinant of the stock price premium. The determinats of the level of forecast accuracy are period, size, age, auditor, underwriter and leverage ratio. It found only underwriter that has significance value to accuracy forecast level. And it also found that squared forecast error was unrelated to the stock price premium upon listing.